Short-term isothermic heat acclimation elicits beneficial adaptations but medium-term elicits a more complete adaptation - Moss, Jodie N. (Eur J Appl Physiol, 2019)
PURPOSE: To investigate the effects of 60 min daily, short-term (STHA) and medium-term (MTHA) isothermic heat acclimation (HA) on the physiological and perceptual responses to exercise heat stress. METHODS: Sixteen, ultra-endurance runners (female = 3) visited the laboratory on 13 occasions. A 45 min sub-maximal (40% W(max)) cycling heat stress test (HST) was completed in the heat (40 °C, 50% relative humidity) on the first (HST(PRE)), seventh (HST(STHA)) and thirteenth (HST(MTHA)) visit. Participants completed 5 consecutive days of a 60 min isothermic HA protocol (target T(re) 38.5 °C) between HST(PRE) and HST(STHA) and 5 more between HST(STHA) and HST(MTHA). Heart rate (HR), rectal (T(re)), skin (T(sk)) and mean body temperature (T(body)), perceived exertion (RPE), thermal comfort (TC) and sensation (TS) were recorded every 5 min. During HSTs, cortisol was measured pre and post and expired air was collected at 15, 30 and 45 min. RESULTS: At rest, T(re) and T(body) were lower in HST(STHA) and HST(MTHA) compared to HST(PRE,) but resting HR was not different between trials. Mean exercising T(re), T(sk), T(body), and HR were lower in both HST(STHA) and HST(MTHA) compared to HST(PRE). There were no differences between HST(STHA) and HST(MTHA). Perceptual measurements were lowered by HA and further reduced during HST(MTHA). CONCLUSION: A 60 min a day isothermic STHA was successful at reducing physiological and perceptual strain experienced when exercising in the heat; however, MTHA offered a more complete adaptation.